Living forms : Romantics and the monumental figure - Haley, Bruce, 1933- (SUNY series, studies in the long nineteenth century., 2003)
"Based on years of archival research in various British and American libraries, Living Forms examines the early nineteenth century's fascination with representations of the human form, particularly those from the past, which, having no adequate verbal explanatory text, are vulnerable to having their meanings erased by time. The author explores a variety of such representations and responses to them, including Coleridge's Shakespeare lectures, Hazlitt's essays on portraits, Keats's poems on mythic and sculpted figures, meditations by Byron's Childe Harold on the monuments of Italy, Felicia Hemans's verses on monuments to and by women, and Shelley's poems and letters on figures from Italy, Egypt, and other antique lands. Haley argues that in what has been called the "museum age," Romantics sought aesthetically to frame these figures as "living forms," mental images capable of realization in alternate modes or forms."--Jacket.